2017
DOI: 10.12741/ebrasilis.v10i2.697
|View full text |Cite
|
Sign up to set email alerts
|

Potencial inseticida de plantas medicinais encontradas na Amazônia Central contra o pulgão-da-couve Brevicoryne brassicae (L.) (Hemiptera: Aphididae)

Abstract: Resumo. O presente trabalho objetivou avaliar o potencial inseticida e a ação repelente sobre o pulgão-da-couve [Brevicoryne brassicae (L.)] de extratos de cinco espécies de plantas ocorrentes e cultivadas na Amazônia Central: Crescentia cujete L., Himatanthus articulatus (Vahl) Woodson, Syzygium malaccense (L.) Merr. & L.M. Perry, Schnella sp. e Protium sp. Os extratos foram utilizados na concentração de 10% e o inseticida botânico a base de azadiractina (Azamax®) foi usado como controle. Para avaliação i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…A study carried out with resin extract of Protium sp. (Breu-white), a species belonging to the same family (Burseraceae), at concentrations of 10% on Brevicoryne brassicae (L.) nymphs, also provided a lower mortality rate of 15,9% within 24 hours (Silva et al 2017b). This shows that this species has a slower effect on aphids.…”
Section: Discussionmentioning
confidence: 94%
“…A study carried out with resin extract of Protium sp. (Breu-white), a species belonging to the same family (Burseraceae), at concentrations of 10% on Brevicoryne brassicae (L.) nymphs, also provided a lower mortality rate of 15,9% within 24 hours (Silva et al 2017b). This shows that this species has a slower effect on aphids.…”
Section: Discussionmentioning
confidence: 94%
“…No studies evaluating the insecticidal activity of other species of the genus Himatanthus on larvae or other stages of the biological cycle of A. aegypti were found in the literature, however, Silva et al (2017) investigated the insecticidal activity of the ethanolic extract of the leaves of H. articulatus (Vahl) Woodson, on the cabbage bean aphid (Brevicoryne brassicae L. (Hemiptera: Aphididae), and observed mortality of 97.6% of the nymphs of this insect. Morais et al (2021) evaluated the insecticidal action of a hydroalcoholic fraction of H. dastricus latex on the infestation of cowpea bean by Callosobruchus maculatus (Coleoptera: Chrysomelidae) and found that this compound caused delays in the larval development of this insect, causing up to 100% mortality of larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Por se tratar de uma foliosa e assim apresentar certa sensibilidade, a cultura da couve é bastante susceptível à incidência de uma série de adversidades, como pragas e doenças. Uma das principais pragas que ocasionam a redução da produção da couve são os pulgões, como Brevicoryne brassicae (Hemiptera: Aphididae), que afetam a planta devido ao seu hábito alimentar sugador, extraindo a seiva da planta, além de agirem como vetores para a transmissão de microrganismos patogênicos [3].…”
Section: Introductionunclassified